2020
DOI: 10.1111/apha.13475
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged therapeutic effects of photoactivated adipose‐derived stem cells following ischaemic injury

Abstract: AimAdipose‐derived stem cells (ASCs) therapies are emerging as a promising approach to therapeutic angiogenesis. Therapeutic persistence and reduced primitive stem cell function following cell delivery remains a critical hurdle for the clinical translation of stem cells in current approaches.MethodsCultured ASCs were derived from subcutaneous white adipose tissue isolated from mice fed a normal diet (ND). Unilateral hindlimb ischaemia model was induced in high‐fat diet (HFD)‐fed mice by femoral artery interrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…A sulfuric acid solution was added to stop the reaction, and the color was analyzed using spectrophotometry at a wavelength of 450 nm [28]. The concentrations of SOD, GPX, GSH, and MDA in the culture media were then calculated according to the standard curve [29].…”
Section: Cardiac Endothelial Cells (Cecs)mentioning
confidence: 99%
“…A sulfuric acid solution was added to stop the reaction, and the color was analyzed using spectrophotometry at a wavelength of 450 nm [28]. The concentrations of SOD, GPX, GSH, and MDA in the culture media were then calculated according to the standard curve [29].…”
Section: Cardiac Endothelial Cells (Cecs)mentioning
confidence: 99%
“…Accumulating studies have demonstrated the benefits of photoactivation as a promising and rapidly expanding physical approach in various pathologies, especially for reducing inflammatory responses and promoting tissue regeneration [12,14,16]. Using our specifically developed device with more refined wavelengths of light, we demonstrated that photoactivation shifted M1-to-M2 ATMs, and transplantation of the treated fat into the visceral adipose tissue improves glucose tolerance in obese mice [14].…”
Section: Introductionmentioning
confidence: 89%
“…Eight-week-old male C57BL/6J mice were fed a high-fat diet (HFD) (TP2330055A; Research Diet, Trophic Animal Feed High-tech Co. Ltd, China) for 16 weeks as described previously [12]. Age-matched male mice that were fed a normal diet were used as controls.…”
Section: Hfd-fed Mouse Modelmentioning
confidence: 99%
See 2 more Smart Citations